2013
DOI: 10.1177/0959683612470175
|View full text |Cite
|
Sign up to set email alerts
|

Mollusks as indicators of historical changes in an estuarine-lagoonal system (Cananéia-Iguape, SE Brazil)

Abstract: Mollusks recovered from three cores taken from the Cananéia-Iguape estuarine-lagoonal system (São Paulo State, Brazil) were studied. The sampled sediments cover a period beginning approximately two centuries ago and end at the present, including a period when the system suffered significant changes of anthropogenic origin – that is, the construction of an artificial channel connecting the lagoon with a nearby river and with the resulting input of fresh water and contaminants generated from mining activity upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
1
15
0
4
Order By: Relevance
“…These studies revealed differences in urban vs. rural areas and also demonstrated the response of the biota at some sites to decreases in waste water discharge, information that can be used to guide the EU's Water Framework Directive (Weckström, 2006;Weckström et al, 2007). In southeastern Brazil, Martínez et al (2013) identified distinct changes in benthic assemblages in the Cananéia-Iguape estuarine-lagoonal system associated with construction of the Valo Grande channel and diversion of freshwater. Analysis of cores from Elkhorn Slough estuary, central California, U.S.A., indicated changes in marsh vegetation that corresponded to changes in sedimentation rates (Watson et al, 2011).…”
Section: Estuaries and Coastal Zonesmentioning
confidence: 99%
“…These studies revealed differences in urban vs. rural areas and also demonstrated the response of the biota at some sites to decreases in waste water discharge, information that can be used to guide the EU's Water Framework Directive (Weckström, 2006;Weckström et al, 2007). In southeastern Brazil, Martínez et al (2013) identified distinct changes in benthic assemblages in the Cananéia-Iguape estuarine-lagoonal system associated with construction of the Valo Grande channel and diversion of freshwater. Analysis of cores from Elkhorn Slough estuary, central California, U.S.A., indicated changes in marsh vegetation that corresponded to changes in sedimentation rates (Watson et al, 2011).…”
Section: Estuaries and Coastal Zonesmentioning
confidence: 99%
“…This group includes mesogastropods of the family Littorinidae (Caenogastropoda), like species of the genus Littoraria Gray, 1833, that adapted to live in these environments (Reid, 1986;Merkt and Ellison, 1998). Because they often present morphological responses to the specific environment they occupy, as well as to human impacts, these mollusks are becoming attractive for use in environmental monitoring (Tanaka and Maia, 2006;Melo et al, 2012;Costa et al, 2013;Martínez et al, 2013). Although mesogastropods are considered less sensitive than neogastropods to some types of chemical contamination (Bauer et al, 1995), these are interesting alternatives to places where there are no neogastropods, as is the case of mangroves.…”
Section: Introductionmentioning
confidence: 99%
“…Within the assumptions for bioindication referred by Mccarty and Munkittrick (1996), L. angulifera meets several selection criteria for estuaries and mangroves monitoring, among them, easy collection and manipulation and its conspicuous presence in these systems. Nevertheless, few studies have used it as a sentinel species of environmental quality in mangroves/ estuaries (Martínez et al, 2013). Recent studies in Southeast (Costa et al, 2013) and Northeast Brazilian coast (Zeidan et al, 2018), suggest the feasibility of using L. angulifera as bioindicator for organotin contamination that still been used in antifouling paints of boats.…”
Section: Introductionmentioning
confidence: 99%
“…From the original dimensions of 4.4 meters wide per 2 meters the channel presently shows widths of approximately 250 meters per depths of about 7 meters. Nowadays, about 60% of the freshwater and suspended sediments carried by the Ribeira River, the most important coastal river in São Paulo, reach the lagoonal system, with a consequent modification of environmental conditions (Martinez et al, 2013) and intense siltation (De Mahiques et al, 2014), forming several islands at the mouth of the artificial channel (figures 4 and 5).…”
Section: The Valo Grande Casementioning
confidence: 99%
“…From the original dimensions of 4.4 meters wide per 2 meters the channel presently shows widths of approximately 250 meters per depths of about 7 meters. Nowadays, about 60% of the freshwater and suspended sediments carried by the Ribeira River, the most important coastal river in São Paulo, reach the lagoonal system, with a consequent modification of environmental conditions (Martinez et al, 2013) and intense siltation (De Mahiques et al, 2014), forming several islands at the mouth of the artificial channel (figures 4 and 5).Furthermore, due to a Pb-mining activity that lasted from 1945 to 1995 in the upstream area of the Ribeira River, the lagoon system received contaminated sediments, with enrichment factors as high as 20 times the natural regional background (de Mahiques et al, 2012) (figure 6). Nowadays, despite the cessation of the mining activities, the system still receives significant quantities of metalenriched sediment since the mining debris are still deposited in the margin of the river (Tramonte et al, 2015).…”
mentioning
confidence: 99%